Multidrug-resistant Pseudomonas aeruginosa infections: current status, challenges, and prospects of phage therapy - Yan, Bo; Yan, Can; Ding, Yafang; Cai, Siyi; Wang, Yujin; Agbo, Elvis; Xu, Xianyun; Qin, Kunhao; Fu, Qiang (Frontiers in Microbiology, 2026)
The emergence of drug-resistant bacterial infections has profoundly impacted global public health. Key pathogens include multidrug-resistant Pseudomonas aeruginosa (MDR-PA), MDR Acinetobacter baumannii, and methicillin-resistant Staphylococcus aureus. Among these pathogens, MDR-PA carries numerous virulence factors that induce extensive tissue destruction. Its inherent ability to form biofilms promotes chronic infection persistence and multidrug resistance, leading to mortality rates up to 40%. Currently, antibiotics remain the mainstay for the treatment of MDR-PA infections. Nevertheless, the escalating prevalence of drug resistance has rendered conventional antibiotic regimens increasingly recalcitrant. Consequently, the imperative for innovative antimicrobial therapeutic modalities to combat Pseudomonas aeruginosa has intensified in the realm of public health. In this context, phage therapy, with its precise bactericidal activity and high host biosafety, has emerged as a compelling alternative. This review provides a comprehensive synthesis of recent advancements in phage therapy targeting MDR-PA, covering clinical applications, current therapeutic approaches, and emerging technological platforms. It further dissects the resistance mechanisms encountered during treatment and puts forward novel counterstrategies to address antimicrobial resistance challenges—including optimized phage-antibiotic synergy, phage genome engineering, and dynamic adaptive therapeutic frameworks—aimed at advancing clinical translation.